A educação das relações étnico-raciais no ensino de Ciências: diálogos possíveis entre Brasil e Estados Unidos - Silva, Douglas Verrangia Corrêa da (Universidade Federal de São Carlos, 2009)
This study aims to understand the education process of Brazilian and American teachers that guide them to live ethnic-racial relationships in their field of work, the teaching of Science. The objective is to establish dialogue between educational processes experienced by these educators and the role assumed by their classes in the education of ethnic-racial relationships among the students. In this dialogue, points converging on the environment where they live and in the educational experiences of these teachers were identified. In the same way peculiarities are highlighted. To achieve the proposed objective, it was necessary to know experiences lived by the participants and their influence in the classrooms where they teach, as well as their views about the social function of science teaching, especially in the context of ethnic-racial relationships. Thus, the interaction between researcher and participants has become central to this study. In the case of Brazil, the encounter was lived in a teacher s preparation course. In the case of US, the encounter was lived in the context of teacher s school environment. The methodology, based on Merleau-Ponty s phenomenology, was useful to identify educational processes produced by experiences and by the thinking about the lived. These processes are constructed in the environment of family, community, teaching practice and in contact with the media. The mentioned spaces are marked by social relationships: ethnic-racial; gender and social class. The learning can lead to the establishment of relations based on racial hierarchies. It also can lead to search for overcoming prejudices and to engage in struggles against racism and discrimination, as well in the valorization of the ethnic-racial diversity. While teachers educate themselves to live ethnic-racial relationships they build guidelines for the Science teaching they develop with the students. In the process of pursuit the study s objective, we also revealed ways in which the teaching of science can contribute to the education of positive/fair, ethnic-racial relationships. These contributions are produced by participants and the researcher in collaboration and refer to activities, political postures that teachers can consider, suggestions of contents and approaches that can provide a Science teaching aligned to the stated assumptions.
Keywords: Professores - formação; Relações raciais; Ensino de Ciências; Ensino de biologia; Ética; Education of the ethnic-racial relationships; Science education; Teachers education; CIENCIAS HUMANAS::EDUCACAO